Water Resources Management and Governance as Part of an Overall Framework for Growth and Development - Tortajada, Cecilia; Joshi, Yugal K. (International Journal of Water Governance, 2013)
Singapore has recognized the importance of universal principles and paradigms in the management of water resources whilst also acknowledging that they do not automatically lead to improvement unless there is a strong emphasis on policy and programme implementation. As a result, the city-state has developed a comprehensive, holistic vision for the overall management of its water resources, making them essential elements for overall development, economic growth and national security. This paper discusses the city-state’s long-term, comprehensive water resources strategies including their policy-making, planning, management, governance and development. It also argues that Singapore is one of the very few countries, if not the only one, that has developed its water policies as part of the overall development goals of the city-state.